Course Modality and Student Outcomes: The Mediating Role of Connection - Ford, Melinda A.; Graden, Bryan S.; Hawkins, Steven R.; Lee, Jonathan E. (Journal of Education and Training, 2024)
During the Covid-19 pandemic, institutions of higher education were required to use multiple teaching modalities, often in the same course, to facilitate student learning, giving students the option of attending face-to-face, attending live over zoom, or watching the recorded lecture videos asynchronously. Simultaneously, some students were forced to enroll in courses with modalities that did not align with what they believed to be most effective for them. This study examines the relationship between accounting students’ perceptions of learning in each modality and course outcomes. Students from nine introductory accounting classes were surveyed on several dimensions of the learning environment. Results demonstrate that the correlation between synchronous attendance (alignment of modality) and course grades is mediated (partially mediated) by students’ connection to their professor. Connection to their professor also fully and directly mediates synchronous attendance on satisfaction and, through sequential mediation in combination with student engagement, also fully mediates alignment of modality on student satisfaction. Regardless of modality (synchronous or asynchronous), or students’ ability to attend the modality that is most effective for their learning, students and professors can improve course outcomes (course grades and course satisfaction) by increasing student-professor connection.